2017
DOI: 10.14814/phy2.13193
|View full text |Cite
|
Sign up to set email alerts
|

Plasma serpinB1 is related to insulin sensitivity but not pancreatic β‐Cell function in non‐diabetic adults

Abstract: Pancreatic β‐cell dysfunction because of reduced β‐cell mass and function is a primary determinant in the progression of diabetes. Increase in β‐cell mass and compensatory hyperinsulinaemia is frequently associated with insulin‐resistant states. Although the humoral factors mediating this compensatory response are unknown, serpinB1, a protease inhibitor, has recently been proposed to be one such factor. In this study, we examine the relationships between plasma serpinB1, insulin sensitivity, and pancreatic β‐c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
0
7
1
Order By: Relevance
“…Moreover, Japanese individuals are thought to have less β-cell mass and be less obese [14], which results in reduced insulin secretion without severe insulin resistance compared to Caucasian subjects. Indeed, in this study, insulin resistance was not severe in T2DM subjects, which may have resulted in relatively low serum SerpinB1 levels compared to those in previous reports in the US [2,4]. The low degree of insulin resistance in subjects with T2DM may enhance the influence of other factors that correlate with insulin sensitivity on SerpinB1 levels.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Moreover, Japanese individuals are thought to have less β-cell mass and be less obese [14], which results in reduced insulin secretion without severe insulin resistance compared to Caucasian subjects. Indeed, in this study, insulin resistance was not severe in T2DM subjects, which may have resulted in relatively low serum SerpinB1 levels compared to those in previous reports in the US [2,4]. The low degree of insulin resistance in subjects with T2DM may enhance the influence of other factors that correlate with insulin sensitivity on SerpinB1 levels.…”
Section: Discussioncontrasting
confidence: 43%
“…Takebayashi et al [3] reported that serum SerpinB1 levels were higher in T2DM subjects than in healthy controls and were negatively correlated with serum low-density lipoprotein cholesterol (LDL-Chol) levels. Using the insulin sensitivity index (SI), Glicksman et al [4] reported that plasma SerpinB1 levels were positively correlated with insulin sensitivity, but not β-cell function in nondiabetic subjects. Kamal et al [5] showed that serum SerpinB1 levels were significantly lower in T2DM subjects than in nondiabetic subjects, positively associated with C-peptide and homeostasis model assessment for β-cell function (HOMA2-%β), and negatively associated with fasting blood glucose (FBG), HbA1c, total cholesterol (T-Chol), and triglycerides (TG).…”
Section: Introductionmentioning
confidence: 99%
“…For 3-year-old BMI z-score, only one probe really stood out in our interaction analyses using the novel framework: a monocyte-specific association with cg12586150 in SERPINB1 , which codes for the monocyte / neutrophil-derived elastase inhibitor and has been found associated with BMI z-score at age 5 in a genome-wide association study [ 53 ]. Plasma levels of serpinB1 have also been associated with insulin sensitivity in non-diabetic adults [ 54 ]. Therefore, further investigations with a focus on the role of specific cell types may be implicated, though these investigations should be undertaken knowing that the estimated monocyte proportion was itself moderately associated with age 3 BMI in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, EL-Ouaamari and coworkers could prove serpinB1 as a novel liver-derived secretory protein that promotes proliferation of human and mouse β-cells (11). Since then, a couple of reports tried to study the possible association of serpinB1 with insulin sensitivity or with type 2 DM (14,27). However, still the genetic variants of the SERPINB1 gene and their association with diabetes have not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, serpinB1 was also previously reported to act as a neutrophil elastase inhibitor (12), and improving glucose tolerance and insulin sensitivity was found to be associated with such inhibition (13). Additionally, a recent report sheds light on the possible association of serpinB1 with insulin sensitivity in healthy adults (14). It is noteworthy that serpinB1 is not the only serpin which could be associated with insulin sensitivity.…”
Section: Introductionmentioning
confidence: 94%